SELF-ACTUALIZATION, SELF-DETERMINATION AND SELF-REALIZATION AS A DRIVING FORCE OF CAREER ORIENTATION - Harkusha Inesa; Andrey Ye. Kryzhanovsky (Alfred Nobel University Publisher, 2020)
The article analyzes the works of Ukrainian and foreign scientists to clarify the essence of the issue which is associated with the personal development of a person, namely, self-actualization, self-determination and self-realization. The results of a detailed analysis of the psychological and pedagogical literature suggest that the concepts of "self-actualization", "self-realization" and "self-determination" should be distinguished despite their semantic relations. It is emphasized that self-determination and self-actualization of the career orientation of university students are directly related to the professional and career orientation. In numerous scientific works, «self-realization» is considered as personal growth, and «self-actualization» as «I have established myself», «I am real». It is argued that the central growth of early youth in general and student age in particular is not only the personal self-determination, but also the professional one. It is also indicated that self-determination is associated with the orientation towards the future, a qualitatively different perception of time, when the present is constantly correlated with the future and is assessed from the perspective of the future. It is noted that it is during the student age that the intensive development of the motivational sphere of the individual takes place, which provides for the formation of moral consciousness and self-awareness. The authors determine that the professional self-determination of young people contributes to the thinking of young people about their future, which contributes to the choice of a profession. It is noted that of particular interest is the question of the subject's ideas about their future and the prospects for their own career development. General tendencies were revealed in students' ideas about the future as a possible construction of their own career. These features appear in the fact that students' image of the future is indistinct, blurred, insufficiently conscious. Three components are characterized: motivational-consumer, value-semantic, and functional-regulatory. It is remarked that self-actualization is an integral attribute of self-awareness and self-development of an individual, and is manifested in the motivational structure, in personal-semantic formations, life-purpose orientations, which find their further embodiment in professional activity, communication, and personal life